Broncoscopia: experiência do Hospital Universitário da Universidade Federal de Mato Grosso do Sul - Patusco, Luiz Armando Pereira (2011)
A descriptive and retrospective study was carried out, starting from the review of 2004 medical registers referring to the bronchoscopy exams done in the pulmonology department of the HU-UFMS University Hospital of the Federal University of Mato Grosso do Sul between March 2001 and March 2011, with analysis of demographic variables, with the aim of characterizing the clinical and epidemiological aspects of this work during the reference period. The association of the variants of sex and age of the patients with the other variants dependent on this study was evaluated through the chi-square test. The other results of the variables evaluated were presented in the form of descriptive statistics or by way of tables or graphs. A total of 1709 registers met the criteria for the study. The exams contemplated patients with ages that varied between 4 and 96 years old, with normal distribution when grouped in to age groups of twenty years, with a predomination of individuals between 41 and 80 years old. The majority of the exams was carried out on males. There was no association between sex and age group. There was a prevalence of patients from the University hospital, HU-UFMS, when compared with other hospital centers and the majority of the exams were requested by pulmonology specialists. Suspicion of neoplasm was the main cause of exam requests. The realization of complimentary procedures such as biopsies and washing did not appear constant. The majority of the exams results had some endoscopic alteration.